Proposta didática para o desenvolvimento de habilidades profissionais nos cursos técnicos em Eletroeletrônica do Instituto Federal do Maranhão - Macêdo, Francisco Cristiano da Silva (2016)
This paper proposed the development of a Didactic Proposal to contribute to the development of Professional Skills of students from the Technical Electronics Course at IFMA in the Electronic Instrumentation discipline in the process of teaching and learning of physics which is the scientific knowledge that make up the content of the discipline. Thus, a documentary analysis about the guidelines was conducted, as well as the, references, conceptualizations of the official documents that deal with the EPTNM that support the development of skills in the disciplines of technical formation. Concerning the specific literature studied, the theoretical foundations for the process of the development of Professional Skills were determined and the development of professional skills in the Teaching and Learning process of Physics in the Electronic Instrumentation discipline from the Technical Electronics Course at IFMA was analyzed. In order to attend this point, the data from 03 classes of this course in one of the units of the Federal Institute of Maranhão that offer the course were collected, totaling 96 students. The data of 03 Physics Teachers who teach or have taught the Electronic Instrumentation discipline were analyzed, as well as the data provided by an Electrical Engineer from a company that hires Electronics technicians and also a Technician from this area inserted in the labor market. Participant observation was also used at this stage. A structured questionnaire was used for the students, and the interview technique was used with the teachers, the Engineer and Technician. The analysis of the students‟ data was performed by using a social scale in which the average ranking is used to calculate the strength of the responses and the preparation of the results, different from the interviews, which permitted to use the content analysis, which was also used to the participant observation. The results showed that it is essential to devote enough time to the practical classes; that adequate theory is necessary (concepts and assumptions) to the development of professional skills that guide the teaching and learning process; that the practical activities should properly translate the practices of a technician in his profession; that Physics is undoubtedly a relevant area relevant in the formation of this technician; that the development of professional skills is relevant to the Technical formation in the High School level and should be part of the technical formation content; that the relation between theory and practice needs more relevance; that teachers need to know more about the identity of the technician in electronics, such as knowing about the profession, areas, challenges, current practices and updates in order to suit the practical activities developed in the process of teaching and learning. These conclusions were the essential basic elements for the construction of our Didactic Proposal along with the chosen literature. The Didactic Proposal was structured in 05 functional units: Directive Teachers, Planning, Execution, Monitoring and Stimuli and Evaluation. The proposal has not been tested empirically; however, it was validated and legitimized by the Delphi Method, one of the best qualitative forecast tools.